Knowledge and practice of standard precautions among healthcare workers of tertiary hospital of Banke district, Nepal - Silwal, Mahesh (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: The healthcare workers are at risk of occupational exposure to blood or air-borne pathogens through contact with human blood, droplets and other body fluids. World Health Organization standardized the precautionary measures which prevent them from contracting and spreading infections among patients or into the community. This study was undertaken to assess the knowledge and practice of standard precautions among the healthcare workers. Method: This is a hospital based observational cross-sectional study done over a period of six months (August 2021 to January 2022) at Nepalgunj Medical College Teaching Hospital which includes 422 participants. The information was recorded via semi-structured proforma. Data were entered in Microsoft Excel 20. Result: The study shows 294 (70%) participants had adequate knowledge about hand hygiene but the practice was found to be 64 (52%), 152 (67%) and 39 (52%) in doctors, nurses and house-keeping staff respectively. The participants, who safely practiced the use of gloves, were 299 (71%). The use or change of masks in each work shift among doctors, nurses and house-keeping staff was found to be 68 (56%), 103 (46%) and 33 (45%) respectively. Only 16 doctors and 109 nurses were trained regarding standard precautions. The study participants responded the hygiene materials were not adequately provided during each work shift. Conclusion: The strategies to facilitate the standard precaution practice should be adopted to ensure prevention of nosocomial transmission of infection. The training programs, provision of hygiene materials and regular supervision will clear the gaps in knowledge and practice of standard precautions.